The Effectiveness of Motor Relearning Programmer (MRP) on Improving Motor Function Among Post Stroke Patients: Literature Review - Agianto Agianto; Bellia Yulise; Rismia Agustina; Ichsan Rizany (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Decreased motor function is one of the problems that often arises in stroke patients. One of the nursing interventions to overcome the decline in motor function in stroke patients is to provide a motor relearning program (MRP) intervention. The objective of this study was to determine the length, duration, and frequency of giving a MRP and the effectiveness of MRP on motor function in stroke patients. This study was conducted by means of a literature review. Eight pieces of literature were identified from three databases (Google Scholar, Pubmed and Science Direct) in the 2000-2020 range. The research design studied was true and quasi-experimental with stroke patient’s population who received MRP . There were eight articles that met the inclusion criteria with different durations and frequencies of motor relearning programs. The provision of MRP interventions in post- stroke patients is effective in improving motor function. There are varying durations and frequencies of giving MRP. Each article mentions that MRP is effective restoring motor function, although with different times, durations and frequencies. Several articles also combined this intervention with other therapies such as bobath therapy and electrical stimulation, the results showed better. The provision of MRP interventions in post- stroke patients is effective improving motor function.